Metabolism and Regulatory Functions of O-Acetylserine, S-Adenosylmethionine, Homocysteine, and Serine in Plant Development and Environmental Responses - Watanabe, Mutsumi; Chiba, Yukako; Hirai, Masami Yokota (Frontiers in Plant Science, 2021)
The metabolism of an organism is closely related to both its internal and external environments. Metabolites can act as signal molecules that regulate the functions of genes and proteins, reflecting the status of these environments. This review discusses the regulatory functions of O-acetylserine (OAS), S-adenosylmethionine (AdoMet), and homocysteine (Hcy), which are key metabolites related to sulfur-containing amino acids in plant metabolic networks, in comparison to microbial and animal metabolism. Plants are photosynthetic auxotrophs that have evolved a specific metabolic network different from those in other living organisms. Although amino acids are the building blocks of proteins and common metabolites in all living organisms, their metabolism and regulation in plants has specific features that differ from those in animals and bacteria. In plants, cysteine (Cys), a sulfur-containing amino acid, is synthesized from sulfide and OAS derived from serine (Ser). Methionine (Met), another sulfur-containing amino acid, is also closely related to Ser metabolism because of its thiomethyl moiety. Its sulfur atom is derived from Cys and its methyl group from folates, which are involved in one-carbon metabolism with Ser. One-carbon metabolism is also involved in the biosynthesis of AdoMet which serves as a methyl donor in the methylation reactions of various biomolecules. Ser is synthesized in three pathways: the phosphorylated pathway found in all organisms, and the glycerate and the glycolate pathways which are specific to plants. This suggests that plants utilize different Ser supply sources depending on its use and environmental circumstances. Among the metabolites in this network, OAS is known to function as a signal molecule to regulate the expression of OAS gene clusters in response to environmental factors. AdoMet regulates aspartate-derived amino acid metabolism at enzymatic and translational levels and may regulate gene expression through the methylation of histone proteins. Hcy is involved in Met‒AdoMet metabolism and can regulate Ser biosynthesis via the phosphorylation pathway at an enzymatic level. This review aims to summarize the regulatory functions of OAS, AdoMet, and Hcy, as signal molecules and compare the available knowledge for plants with that for animals and bacteria and propose a future perspective on plant researches.